The Role of Halal Certification Institutions in Ensuring Production Safety, Product Quality, and Economic Development: Evidence from Makassar, Indonesia - Reslawati, Reslawati; Fauziah, Fauziah; Amir, Muhammad; Wahab, Abdul Jamil; Rosidi, Achmad (Samarah: Jurnal Hukum Keluarga dan Hukum Islam, 2026)
This study examines the role of halal certification bodies in safeguarding production safety, identifies the challenges encountered in the certification process, and analyzes the implications of halal certification for strengthening the competitiveness of MSMEs in Makassar City, South Sulawesi. Employing a qualitative case study design, data were collected through in-depth interviews with purposively selected informants, complemented by participant observation and document analysis. The data were analyzed using thematic analysis with source and methodological triangulation to enhance the credibility of the findings. The results demonstrate that halal certification bodies play a pivotal role in ensuring production safety by conducting compliance audits, verifying production processes, facilitating laboratory testing, and providing technical guidance on halal assurance standards. Halal certification also enhances consumer confidence, broadens market opportunities, stimulates product innovation, and improves the income and competitive capacity of MSMEs. Nevertheless, the effectiveness of the certification system is constrained by high certification costs, bureaucratic complexity, and inadequate technical support, particularly for small-scale enterprises. The findings underscore the importance of stronger collaboration among government agencies, halal certification institutions, universities, and business actors to develop a more efficient, inclusive, and sustainable halal certification ecosystem that supports regional halal industry development and MSME competitiveness